Wringing watts from waves a high schooler's invention turns water motion into "juice". - Jones, W.D.
Generating electricity from wave power is an old idea that gained new life when the quest for alternative energy sources began in the 1970s. This paper describes how the 17-year-old, Aaron Goldin, found an elegant way to do the job with a buoy, a gyroscope, and a generator. Goldin invented the "autonomous gyroscopic ocean-wave-powered generator", cobbled together from parts scavenged from an old tape recorder and other household appliances. Unlike several other wave-power devices now being tested, Goldin's invention requires no hydraulics or other intermediate systems to transfer power to the generator.
Keywords: Alternative energy source; Autonomous gyroscopic ocean-wave-powered generator; Buoy; Gyroscope; Wave power